Differentiation and species status of the Neotropical yellow-eared bats Vampyressa pusilla and V-thyone (Phyllostomidae) with a molecular phylogeny and review of the genus - Lim, B. K.; Pedro, Wagner André [UNESP]; Passos, F. C. (Museum & Inst Zoology Pas-polish Acad Sciences, 2003)
A systematic re-evaluation of Vampyressa pusilla warrants the elevation of V p. thyone from subspecies to species rank based on its distinction from the allopatric V p. pusilla. Morphological, mensural, chromosomal, and mitochondrial differences define each of these two taxa as divergent lineages. Vampyressa pusilla is endemic to the Atlantic Forest of southeastern South America and V thyone is found allopatrically in northwestern South America, Central America, and southern Mexico. A molecular phylogenetic analysis of the mtDNA ND3-4 gene region using restriction endonuclease cut sites resulted in a monophyletic, although weakly supported Vampyressa ingroup with Chiroderma, and a clade of Mesophylla and Ectophylla as successive basal outgroup lineages. The phylogeny within Vampyressa, with the exception of V melissa which is most similar to V thyone based on karyotypes and morphology, had a topology of ((pusilla + thyone) + ((brocki + nymphaea) + bidens))).
Keywords: Chiroderma; Ectophylla; Mesophylla; morphology; Phyllostomidae; restriction site mapping; Vampyressa; Vampyressa pusilla; Vampyressa thyone